MVNC: A Multiview Network Computer Architecture - Yu, Hongliang; Zheng, Weimin; Shen, Meiming (Computing and Informatics, 2012)
In this paper, MVNC, a multiview network computer system for a high usability thin-client computing environment, is introduced. MVNC uses a revised SBC model to offer a new framework for thin client computing. MVNC can be used as a full functional Windows machine, or used as a Linux workstation, or a~graphic terminal. Its multiview work style is achieved by the attempts on GUI seamless integration technology, device integration technology and local video playback support. MVNC is implemented in an embedded Linux environment using a MIPS-4KC microprocessor. Test results on video application show that MVNC system uses its client hardware more efficiently and the load of MVNC server is lightened.